Welfare effects of the allocation of talent to financial trading: What does the Grossman-Stiglitz model say? - Lutz Arnold; Sebastian Zelzner (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
This paper investigates the implications of the Grossman-Stiglitz (1980) model on the informational efficiency of financial markets for the optimality of the allocation of talent to financial trading versus entrepreneurship. Informed traders make the financial market more informationally efficient, entrepreneurs create output and jobs. The model indicates that financial trading attracts too much, rather than too little, talent.
Keywords: G14; J24; 330; market efficiency; asymmetric information; allocation of talent; occupational choice